Factors affecting relative efficiency of higher education institutions of economic orientation - Arbula Blecich, Andrea (Array, 2020)
This paper investigates the factors that influence the relative efficiency of higher education institutions of economic orientation. The empirical analysis is carried out on 31 higher educational institutions of economic orientation in Croatia, Slovenia and Bosnia and Herzegovina, in three phases. In the first phase, relative efficiency of observed institutions is evaluated for three main areas of their activities: teaching, research and international activity. In the second phase, higher education institutions are clustered based on relative efficiency results of each individual area of their activity. In the last, third phase, key association factors of a particular cluster are determined using univariate binary logistic regression and odds for transition to a more favourable cluster are defined. The results indicate that odds for positioning in the more efficient cluster are higher in public institutions than in private ones, in institutions with more published professional papers, in those with higher expenditures per faculty, the larger number of enrolled students per faculty, as well as in those with more visiting researchers. The proposed model can serve as a design guideline for education policies and as a moderation guideline for national authorities.